PREFIXES, SUFFIXES, AND INFIXESES IN KURMANJI (ZAZAKI) (Comparative descriptive study) - Malmîsanîj, Mehmet T.; Mosa, Abdulwahab X. (Humanities Journal of University of Zakho, 2017)
This research "Prefixes, Suffixes, and Infixeses in Kurmanjki (Zazaki) is prepared on the basis of comparison to other dialects. The materials are taken from oral and written Kurmanjki resources. One of the aims of this research is to compare prefixes, suffixes, and infixeses of two Kurdish dialects, Kurmanjki and Kurmanji, their mutual and diffident sides to be shown. In the recent times, in Kurmanjki and Kurmanji, new terms and words are inflected. To inflect new words and terms, we should have knowledge about prefixes, suffixes, and infixeses. Another aim of this research is to know the characteristics of Kurmanjki’s prefixes, suffixes, and infixeses, and to help inflecting oral words. In this research, several outcomes were shown in the conclusion. Key words, Kurmanjki, Kurmanji, Kurmanjki infixeses, Kurmanjki prefixes, Kurmanjki suffixes, Zazaki.